Peran Kepemimpinan Dalam Upaya Peningkatan Kompetensi Guru Madrasah Aliyah Di Provinsi Bengkulu - Khairiah Khairiah (At-Ta'lim : Media Informasi Pendidikan Islam, 2020)
Abstract: The Role of Leadership in Efforts to Improve Competency of Madrasah Aliyah Teachers in Bengkulu ProvinceTeacher competence has not increased even though there is a certification policy. Leadership is a solution as a mediator in providing justification, learning agent, facilitator, motivator, engineer and inspiration for teachers and students in the interests of teacher competence. The purpose of writing is to describe efforts to improve teacher competence using descriptive qualitative methods. The components that become benchmarks are teacher behavior and leadership in carrying out their main duties, functions and responsibilities as educators. The results of research on the Teacher Competency Improvement Training (PKG) show that teacher competence is not as expected, namely showing pre-test scores of 39, 48 and posttests 44, 49. Leadership has a strategic role in efforts to improve teacher competence, collaborating with institutions for understanding the quality of achievement teacher competence in an effort to achieve increased teacher competence.